2004
DOI: 10.1007/s00466-004-0610-0
|View full text |Cite
|
Sign up to set email alerts
|

A meshfree weak-strong (MWS) form method for time dependent problems

Abstract: A meshfree weak-strong (MWS) form method, which is based on a combination of both the strong form and the local weak form, is formulated for time dependent problems. In the MWS method, the problem domain and its boundary are represented by a set of distributed field nodes. The strong form or the collocation method is used to discretize the time-dependent governing equations for all nodes whose local quadrature domains do not intersect with natural (derivative or Neumann) boundaries. Therefore, no numerical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 15 publications
(25 reference statements)
2
20
0
Order By: Relevance
“…This agrees well with those derived from other methods, e.g., the MK (Bui et al, 2011a,b), MWS (Gu and Liu, 2005), or LoKriging (Li et al, 2004).…”
Section: Tablesupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees well with those derived from other methods, e.g., the MK (Bui et al, 2011a,b), MWS (Gu and Liu, 2005), or LoKriging (Li et al, 2004).…”
Section: Tablesupporting
confidence: 91%
“…We have also extended their applicability to study free vibrations of piezoelectric structures for which the electric and the mechanical fields are coupled. It is shown that the numerical results obtained with the CQ4 element agree well with those reported in the literature and obtained by such methods as the boundary element method (Manolis and Beskos, 1988), the FEM (Petyt, 2010;Miranda et al, 2008;Dai and Liu, 2007), mesh-free methods (Bui et al, 2011a,b;Bui and Nguyen, 2011;Kosta and Tsukanov, 2014;Sadeghirad et al, 2009;Cui et al, 2010;Gu and Liu, 2005), and the isogeometric analysis (Valizadeh et al, 2013;Cottrell et al, 2006).…”
Section: Introductionsupporting
confidence: 82%
“…Some research work has been done to get rid of the shear locking phenomena, e.g., adding the transverse shear strain as another variable in MLPG [6]. The shear locking phenomena could be easily avoided by simple using the high order meshless shape function (more than four interpolation nodes) in the meshless method [12,17]. There is no difficulty to satisfy this requirement in 1-D problem.…”
Section: Validation Example: Static Analysis Of a Fixed-fixed Thin Beammentioning
confidence: 98%
“…Onate et al [14] introduced a stabilization technique by adding artificial terms in both governing equations and Neumann boundary conditions, however, these terms only serve the stabilization purpose and their suitability is restricted to some special problems. Liu and Gu [15,16] proposed a meshfree weak-strong-form method, in which the weak form is applied to the subdomain concerned with Neumann boundary conditions and strong form to the one with Dirichlet boundary conditions. Pan et al [17] presented meshless Galerkin least-squares method by making use of Galerkin method in the boundary domain and least-squares method in the interior domain.…”
Section: Introductionmentioning
confidence: 99%